p53 Mediates TNF-Induced Epithelial Cell Apoptosis in IBD - Goretsky, Tatiana (American Society for Investigative Pathology, 2012)
Chronic ulcerative colitis (CUC) is characterized by increased intestinal epithelial cell (IEC) apoptosis associated with elevated tumor necrosis factor (TNF), inducible nitric oxide synthase (iNOS), and p53. We previously showed that p53 is increased in crypt IECs in human colitis and is needed for IEC apoptosis in chronic dextran sulfate sodium-colitis. Herein, we examined the roles of TNF and iNOS in regulating p53-induced IEC apoptosis in CUC. The IEC TUNEL staining, caspases 3, 8, and 9, and p53 protein levels, induced by anti-CD3 monoclonal antibody (mAb) activation of T cells, were markedly reduced in TNF receptor 1 and 2 gene knockout mice. Induction of IEC apoptosis correlated with increased p53, which was attenuated in iNOS(−/−) mice. IEC p53 levels and apoptosis were reduced in IL-10(−/−) colitic mice treated with neutralizing TNF mAb and the iNOS inhibitor, aminoguanidine, further suggesting that TNF and iNOS are upstream of p53 during colitis-induced IEC apoptosis. IEC apoptosis and p53 levels were assessed in control versus untreated or anti-TNF–treated CUC patients with equivalent levels of inflammation. Data indicated that IEC apoptosis and p53 levels were clearly higher in untreated CUC but markedly reduced in patients treated with anti-TNF mAb. Therefore, TNF-induced iNOS activates a p53-dependent pathway of IEC apoptosis in CUC. The inhibition of IEC apoptosis may be an important mechanism for mucosal healing in anti-TNF–treated CUC patients.